2018
DOI: 10.31015/jaefs.18031
|View full text |Cite
|
Sign up to set email alerts
|

A review: secondary metabolites of Uvaria chamae p. Beauv. (Annonaceae) and their biological activities

Abstract: The primary metabolites are of major importance to plants, while the secondary metabolites are of medicinal value to man (Trease and Evans, 1989) and these can equally be obtained from various anatomical structures of plants (Fahn, 1974). Man has benefited from the presence of these chemicals by exploiting the plant products as sources of sustenance in a variety of ways. For example, many drugs today are of plant origin. Pharmacological history is abounding with examples such as quinine, aspirin, picrotoxin, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 88 publications
0
10
0
Order By: Relevance
“…Uvaria chamae P. Beauv. (Annonaceae) is a WEP providing-species which occurs in tropical West and Central Africa within tropical dry and moist forests [ 10 , 11 ]. The species occurs at higher densities in gallery forests of the Guinean and Sudanese savannas on rocky, and cooler soils (in plains and valleys) in Senegal, Cameroon and the Democratic Republic of Congo [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Uvaria chamae P. Beauv. (Annonaceae) is a WEP providing-species which occurs in tropical West and Central Africa within tropical dry and moist forests [ 10 , 11 ]. The species occurs at higher densities in gallery forests of the Guinean and Sudanese savannas on rocky, and cooler soils (in plains and valleys) in Senegal, Cameroon and the Democratic Republic of Congo [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the light of modern medicine, Uvaria chamae plant parts and extracts has been proved by several researchers to be quite efficacious. Abu et al [5] showed that several researches on the biological contents and activities of secondary metabolites accumulated in Uvaria chamae and its plant parts in the light of modern medicine are truly biologically active and validates their claims in traditional system of medicine. Extensive literature on anti-inflammatory activity of Uvaria species showed that its extracts and isolates exhibited significant anti-inflammatory activity through various established mechanism of action [6].…”
Section: Introductionmentioning
confidence: 94%
“…This is apparent in causing increase in mount frequency, intromission frequency, erection frequency and penile erection while causing decreases in mount latency, intromission and post ejaculatory intromission. This showed that the extract and it fractions possess the potential for sexual libido and potency [12,80] . The chemical constituents of Uvaria Chamae include; pinostrobin, uvaretin, nantenine, chamanetin, nornatine and corydine as shown in Figure 28.0 [80] .…”
Section: Purple Cornmentioning
confidence: 99%
“…This showed that the extract and it fractions possess the potential for sexual libido and potency [12,80] . The chemical constituents of Uvaria Chamae include; pinostrobin, uvaretin, nantenine, chamanetin, nornatine and corydine as shown in Figure 28.0 [80] . Its aphrodisiac action could be ascribed to the presence of carotenoid, vitamins, flavonoids, minerals and amino acids such as cyanidin, gallic acid, hibisic acid, citric acid, kaempferol, quercetin-3-rutinoside and catching figure 30.0 [43,81,82] .…”
Section: Purple Cornmentioning
confidence: 99%